PERBEDAAN METODE SCRAMBLE DENGAN METODE WORD SQUARE TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INGGRIS MATERI PARTS OF HUMAN BODY: Studi pada Siswa Kelas III SDIT At-Taufiq Kota Tangerang - Desa, Putri Emma Kurnia; Rosnaningsih, Asih; Nurjaman, Iman (JURNAL PENDIDIKAN DASAR NUSANTARA, 2018)
This study aims to determine differences in student learning outcomes in English subjects in two classes, with first experimental class using scramble method and second experimental class using word square method. This type of research is quantitative research with quasi experiment type. In this research the sampling technique using saturated sampling technique. The sample in this research is the students of class IIIA and students of class IIIB at SDIT At-Taufiq Tangerang City. Instruments in this study using objective tests in short form. Based on the calculation using t-test, it is found that t-count > t-table (3,1> 2,011) at significant level α = 0,05. The average score in experimental class I using scramble method is 69.58 and the average score in experiment class II using word square method is 78.2. So the word square method is better than scramble method. Keywords: scramble method, word square method, student learning outcomes